What intensity of exercise is most suitable for the elderly in China? A propensity score matching analysis - Chen, Xinlin; Su, Dai; Chen, Xinlan; Chen, Yingchun (BMC public health, 2021)
The strategy of successful ageing is an important means to deal with the challenges of the current ageing society. This paper aims to explore the effects of different intensities of physical activity on the successful ageing of the elderly. Our data were from wave 4 of the China Health and Retirement Longitudinal Survey (CHARLS), involving 9026 residents aged 60 years and older. The intensity of physical activity was divided into three levels: vigorous, moderate and mild. The concept of successful ageing adopted a four-dimensional model of life satisfaction added to the theoretical model of Rowe and Kahn's. Propensity score matching (PSM) with controlling nine confounding factors were used to analyse the effects of different intensities of physical activity. The percentage of successful ageing was 1.88% among all subjects. Among them, 30.26, 29.57 and 29.40% of the elderly often participated in vigorous, moderate and mild physical activity, respectively. The results of PSM showed that participation in moderate activity increased the probability of successful ageing of the elderly by 0.76-0.78% (P < 0.001), while participation in vigorous and mild physical activity had no significant effect on successful ageing (P > 0.05). Moderate physical activity had statistically significant effects on four components of successful aging, including major disease, physical function, life satisfaction, and social participation (P < 0.05). Moderate-intensity physical activity was most beneficial to the successful ageing of the elderly and should be promoted in the elderly population.